Natyasastra of Muni Bharata - Bharata Muni; Tripathi,Kamalesh Datta.,ed.; Tiwari,Narendra Dutt.,ed. (New Delhi Indira Gandhi National Centre For The Arts, 2015)
Contents :v.1.(Chapter I-XIV) (lxxxiii,451 p.)
Keywords: Theatre -- India; Sanskrit drama -- History and criticism; Music-India -- History and criticism